ANALISIS TRANSMISI KEBIJAKAN MONETER MELALUI JALUR PINJAMAN BANK DI INDONESIA - Violetta Puteri Dhuayu; Sri Ulfa Sentosa; Selli Nelonda (Universitas Negeri Padang, 2017)
This study aims to determine and analyze the influence of interest rate and bank-specific to bank loans growth and also analyze the causality between interest rate, bank loas growth and economic growth with inflation rate in Indonesia. The type of this research is descriptive and associative. This research used secondary data from 2006 Q1 to 2015 Q4 obtained from the related institution which is analyzed by using the Ordinary Least Square (OLS) method and Vector Autoregerssion (VAR). The results show that interest rate (BI Rate) affect bank loans growth in Indonesia while, bank liquidity and bank capitalization positively affect bank loans growth in Indonesia. It also show that there are causality between interest rate and bank loans growth with inflation rate in Indonesia.